Articular Cartilage Defects of the Knee Diagnosis and Treatment - Rodrìguez-Merchán, E. Carlos.; Rodrìguez-Merchán, E. Carlos. (Springer Milan : Imprint: Springer, 2012)
This book reviews current knowledge on the diagnosis and treatment (surgical and non-surgical) of cartilage defects at the knee joint. In the discussion of diagnosis, the focus is primarily on imaging findings, particularly those obtained with MRI. The remainder of the book is devoted to the full range of current conservative and surgical treatments, with attention to both treatment indications and results as reported in the recent literature. In reviewing non-surgical treatment, oral and intra-articular medical management is evaluated and rehabilitation and physical therapy are also considered. The three main types of surgical technique – microfracture surgery and similar procedures, mosaicplasty and related techniques, and autologous chondrocyte transplantation – are then extensively discussed in a series of highly informative chapters. This book will be of great practical value for clinicians, assisting in daily decision making.